2009
DOI: 10.1017/s0954579409000534
|View full text |Cite
|
Sign up to set email alerts
|

Representations of the caregiver–child relationship and of the self, and emotion regulation in the narratives of young children whose mothers have borderline personality disorder

Abstract: Borderline personality disorder (BPD) represents a severe distortion in the development of attachment, self, and emotion regulation. Study of children at high risk of developing BPD may inform precursors to BPD. In a low socioeconomic status sample of 30 children aged 4–7 whose mothers have BPD and 30 normative comparisons, representations of the caregiver–child relationship and of the self, and emotion regulation were assessed with a story-stem completion measure. In contrast to comparisons and controlling fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 112 publications
1
72
0
2
Order By: Relevance
“…In a study using a story-stem completion measure to assess self-other representations and emotion regulation, children of mothers with BPD provided narratives about parent figures with significantly more role reversal, fear of abandonment, and negative parent-child relationship expectations than did children of mothers without BPD [50]. The children of mothers with BPD also provided narratives with more incongruent and shameful selfrepresentations than did the comparison children.…”
Section: Parents With Borderline Personality Disorder and Child Funcmentioning
confidence: 99%
“…In a study using a story-stem completion measure to assess self-other representations and emotion regulation, children of mothers with BPD provided narratives about parent figures with significantly more role reversal, fear of abandonment, and negative parent-child relationship expectations than did children of mothers without BPD [50]. The children of mothers with BPD also provided narratives with more incongruent and shameful selfrepresentations than did the comparison children.…”
Section: Parents With Borderline Personality Disorder and Child Funcmentioning
confidence: 99%
“…Schacht et al 16 found that preschool-aged children of women with BPD had poorer theory of mind when given a false-belief task, and were poorer at both labelling pictures of emotional faces and identifying possible causes of the depicted emotions. Macfie and Swan31 found that their children aged 4–7 years of mothers with BPD displayed more negative self-representations, more fantasy-proneness and fantasy-reality confusion, lower narrative coherence and more intrusion of traumatic material when participating in a series of role-play scenarios, when compared with children of healthy mothers. Abela et al 32 found their children aged 6–14 years of mothers with BPD to have a more negative attribution style, more dysfunctional attitudes, a more ruminative response style, engage in more reassurance-seeking, and have higher levels of self-criticism than a sample of children of depressed mothers.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies showed that children of mothers with BPD had elevated instances of disrupted attachment styles 21 29 31 32. Additionally, in role-play tasks, children of mothers with BPD (aged 4–7 years) showed excessive role-reversal,31 and fear of abandonment in their relationships with their parents, and more negative expectations of these relationships.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…QR can be approached as a combination of behaviors, feelings, and expectations that are unique to a particular caregiver and a particular child. It is a broad concept encompassing both positive dimensions such as closeness, responsiveness, warmth, involvement, support, and positive affect, and negative dimensions such as negative affect, criticism, intrusiveness, irritability, control, and harsh discipline (MacFie & Swan, 2009;McCall, Groark, & Fish, 2010;Recchia, 2012;Vu, Hustedt, Pinder, & Han, 2015). Significant relations between QR with caregivers and children's EB have been widely reported in previous studies, both cross-sectionally and longitudinally (Caspi et al, 2004;Daley, Renyard, & Sonuga-Barke, 2005;Peris & Baker, 2000).…”
mentioning
confidence: 94%